Zircon U Pb age constraints on the mid-Cretaceous Hkamti amber biota in northern Myanmar - Xing, Lida; Qiu, Liang (Palaeogeography, palaeoclimatology, palaeoecology, 2020)
Hkamti amber contains exquisite fossils, but the age of the amber biota is unclear. In this study, we documented the characteristics of fossils hosted in the amber, and we present zircon UPb ages of tuff layers from the Kachin and Hkamti sites (i.e., the “new mine”). We also present a compilation of arthropod and echinoderm syn-inclusions from the mid-Cretaceous Hkamti amber of Myanmar, indicating a humid tropical or subtropical forest paleo-environment. Zircon analyses (n = 143) of four tuff samples that host the amber deposit in different pits yielded a weighted-mean age of 109.7 ± 0.4 Ma. Zircon rare earth element data demonstrate the zircons are of igneous origin. Therefore, the age of the Cretaceous amber biota from Hkamti is ca. 110 Ma. This means that the Hkamti assemblage should be treated as distinct from other Burmese amber collections, as it represents a significantly older source within a different depositional environment. The commercial sources of Burmese amber are variable and encompass multiple mining regions, which makes maintaining distinctions between deposits important if their faunal contents are to be studied in a proper temporal or ecological context. The refined understanding of amber deposits in Myanmar highlights the importance of distinguishing sources, but it also offers an opportunity to study a series of deposits from ~110 to ~72 Ma, instead of just one snapshot of terrestrial ecology around ~99 Ma.